Transmission of Fossil Energy to Renewable Energy in Indonesia: Case Study 1990-2020 - Febrianti, Dewi Anisa; Hidayah, Nur (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The existence of an energy emergency in Indonesia means that there must be a transition from the fossil energy using to renewable energy to achieve energy security. The increasing level of demand for fossil energy in Indonesia is causing fossil energy reserves to become increasingly depleted. The processing carried out also has a very bad impact on the environment because it causes carbon dioxide emissions. The use of renewable energy is highly recommended because data obtained from the Directorate General of EBTKE potential for renewable energy comes from hydropower, geothermal, bioenergy, solar, wind and marine energy. So the purpose of this research is to analyze the influence of population growth, foreign direct investment (FDI), carbon dioxide emissions, fossil energy consumption and world oil prices on the use of renewable energy. Methodology: This research used Ordinary Least Square (OLS) to analyze the influence of population growth, foreign direct investment (FDI), carbon dioxide emissions, fossil energy consumption and world oil prices on the use of renewable energy. Followed by classic assumption tests in the form of: multicollinearity test, residual normality test, autocorrelation test, heteroscedasticity test and model linearity test which is then continued by carrying out a stationarity test (unit root test), cointegration test. The data used in this research is secondary data sourced from the World Bank, Statistics and Our World in Data. Results: In this study, the results obtained were that population growth did not have a significant effect on the use of renewable energy because the t test results obtained were 0.3357 > 0.10, while foreign direct investment has a value of 0.0001 < 0.05, carbon dioxide emissions 0.0215 < 0.05, fossil fuel consumption 0.0440 < 0.05, and oil prices 0.0008 < 0.05 so that in the fourth variables have a significant influence on the use of renewable energy in Indonesia. Applications/Originality/Value From the study can be seen that the implementation of renewable energy can be used as a policy by the government to reduce various impacts such as energy security and reduce carbon dioxide emission problems. Steps that the government can take are to utilize the potential of renewable energy in Indonesia by making it environmentally friendly fuel that can be used as a fuel substitute, and so that in the future this condition can improve the increasingly deteriorating air quality in Indonesia.